Behind the veil : resistance, women, and the everyday in colonial South Asia - Ghosh, Anindita, 1967- (Delhi : Permanent Black : Distributed by Orient Longman, 2007)
Contributed articles with special reference to India.
Includes bibliographical references and index.
Keywords: Feminism -- India -- History; Women -- India -- History; Women -- India -- Social conditions